The Current Concept and Role of Intensive Cardiovascular Care Units - Siska Suridanda Danny (Heart Science Journal, 2023)
Since its first establishment in the early 1960s, intensive care for the critically ill cardiac patients had transformed substantially. From a unit designed only to monitor cardiac rhythm and administer electrical therapy to patients with myocardial infarction (MI), the Intensive Cardiovascular Care Units (ICVCU) now provide care for a wide array of patients with cardiovascular conditions needing close observation and hemodynamic support. This shift in role is accompanied with the development of cardiac critical care as an emerging subspecialty of cardiovascular medicine. Cardiac intensivists should have proper training in general cardiology, combined with additional competency in critical care, including mechanical ventilation, renal replacement therapy, mechanical circulatory support and general preventive measures for infections. A high-intensity medical staffing in a closed care system had shown to improve mortality in critically ill cardiac patients in the contemporary ICVCUs. As interventional cardiology, structural heart disease, electrophysiology, advanced heart failure and transplantation continue to offer new treatment options for complex high-risk patients, cardiac critical care is of utmost importance to provide collaborative care among these disciplines.